OPTIMIZATION OF LEAFLET MEDIA IN DIABETES EDUCATION FOR ADOLESCENTS AS A PREVENTION STRATEGY IN THE SETIARATU VILLAGE OF TASIKMALAYA CITY - Peni Cahyati Peni Cahyati; Dudi Hartono Dudi Hartono; Dewi Aryanti Dewi Aryanti; Yudi Triguna Yudi Triguna; Tetet Kartilah Tetet Kartilah; Kusmiyati Kusmiyati; Sofia Februanti Sofia Februanti; Novia Indriani Novia Indriani; Novi Enis Rosuliana Novi Enis Rosuliana; Syaukia Andini Syaukia Andini (Jurnal Pengabdian Masyarakat DEDIKASI, 2025)
Diabetes mellitus (DM) is a non-communicable disease whose prevalence continues to increase, including among adolescents. Lack of knowledge and awareness among adolescents about risk factors and prevention of DM can increase the likelihood of developing DM in adulthood. This community service activity aims to optimize the use of leaflets in educating adolescents about diabetes mellitus as an early prevention strategy. The method of implementation includes providing health education using leaflets containing information about DM, risk factors, signs and symptoms, and prevention efforts through the application of a healthy lifestyle. The target of this activity is adolescents living in the Setiaratu Village, Cibeureum District, Tasikmalaya City. This activity was carried out as part of the Tasikmalaya Health Polytechnic's IPTEKS community service program for the community (IbM). The activity was carried out in October 2025. The training results showed that adolescents' knowledge scores about diabetes mellitus increased by 30 points compared to before. Statistically, using the Wilcoxon test, the results showed a difference in the average knowledge scores before and after training, with a significance level of ρ = 0.0001 (ρ < 0.05). It is hoped that after receiving this training, adolescents will contribute to increasing public knowledge about Diabetes Mellitus. Thus, the optimization of leaflets has proven effective as a health education tool in increasing adolescents' awareness and knowledge about Diabetes Mellitus as an early prevention effort.